Application of ergonomics in Latin American offices - Yalo Sullcaray , Bertha (2023)
The application of ergonomics at work is based on the first ergonomic disorders that people who suffered from similar ailments received, since these present more risks in offices and that there may be more possibility that they suffer injuries and pain as time goes by, the which ergonomically designed equipment was established to help protect workers from one or more musculoskeletal disorders. Ergonomics is a science that studies the key tools to design, evaluate and redesign workplaces in organizations to the dangers that each one of them is exposed to in order to model a system that safeguards its integrity, reduces risks, such as bad posture at work, considerably reducing during implementation the program is divided into five stages, which are carried out by the workers: analysis of the company, evaluating ergonomic risks, development and implementation of the action plan, and follow-up of the rules to the control measures, with the intention that this analysis allows to know the levels of risk that are exposed and provide solutions such as reducing working hours, also reducing health expenses by the company as well as locating the break points that can be modified. places and comfortable areas for the well-being of the worker. The purpose of this systematic review is to continuously improve working conditions and promote the practice of commitment to society in the workplace and minimize the work risks that may affect employees, helping workers to be more efficient in their workplace. This research was carried out based on the PRISMA methodology, for the development study search engines such as SCIELO, SPRINGER LINK, PROQUEST and GOOGLE ACADEMIC, REDALYC were used using delimiting criteria within which journals from 2010 - 2022 were used, both in Spanish and English. From this review we will try to promote working conditions and through its social practice rooms and the implementation of the way to seek to improve and promote the conditions of the worker and the ergonomics of the worker's health where they recognize the importance of their evaluations, which allow improving the quality of life of the employees of these work environments, the organizations, and allow their socio-technical systems to become healthier and stronger systems. In such a way that they have training on the sport that they can do from their seats in order to avoid health problems.